Properties of Priestia megaterium 035 Keratinase - Avdiyuk, K.V.; Varbanets, L.D.; Shtenikov, M.D.; Ivanytsia, V.O.; Авдіюк, К.В.; Варбанець, Л.Д.; Штеников, М.Д.; Іваниця, В.О. (PH "Akademperiodyka" of the NAS of Ukraine, 2025)
In the modern world, the problem of the disposal of animal husbandry waste is very acute, because the growing volume of production leads to an increase in the amount of waste, which, if handled improperly, can pose a threat to the environment. Poultry factories, slaughterhouses, the leather, fur, and wool industries, and hairdressing plants constantly produce millions of tons of keratin-containing waste in the form of feathers, pig bristles, hooves, horns, leather, wool, and hair. The development of methods for their environmentally friendly processing using enzymes of microorganisms, in particular proteases, to obtain valuable products such as amino acids and oligopeptides is an important task of modern biotechnology. The purpose of this work was to investigate some physicochemical properties (pH- and thermooptimum, pH- and thermostability, substrate specificity) of the Priestia megaterium 035 enzyme preparation with keratinase activity. Methods. The object of investigation was P. megaterium 035 isolated from the bottom sediments of the Black Sea. The culture was grown under conditions of submerged cultivation at 28 °C, with a nutrient medium stirring rate of 232 rpm for 5–7 days. For growth, a basic nutrient medium containing 0.5% defatted chicken feathers as the only source of carbon and nitrogen was used. Keratinase activity was assessed by UV absorption at 280 nm of the hydrolysis products of keratin-containing materials. The degree of substrate hydrolysis was estimated by the ratio of the initial and final weights of the substrate. To investigate the substrate specificity, the P. megaterium 035 culture was grown in 50 ml test tubes with such substrates as white and black chicken feathers, sheep, rabbit, cat, and dog wool, pig bristles, and children's nails and hair. Results. The culture of P. megaterium 035 was grown for 5–7 days on a nutrient medium with the addition of white chicken feathers as the only source of carbon and nitrogen, the degree of hydrolysis of which was 84%. A partially purified enzyme preparation with keratinase activity was obtained by the method of 90% saturation of the supernatant of the P. megaterium culture liquid with ammonium sulfate. The studied enzyme preparation was active in a wide pH range (7.0–12.0) with three activity optima (7.0, 10.0, and 12.0). It was found that the enzyme was completely stable at pH 11.0 and retained 78% of the initial activity at pH 10.0 after 24 h of incubation. At neutral and slightly alkaline pH values, the enzyme preparation was less stable: its activity at pH 7.0–9.0 was maintained for 3 h. A temperature of 50 °C was optimal for the studied preparation. The enzyme retained 100% activity at 50 °C after 30 min of incubation, 91% and 25% after 60 min and 120 min of incubation, and at 60 °C it showed 80% of the initial activity only after 15 min of incubation. It was shown that P. megaterium effectively decomposed only white chicken feathers (84%), worse – black chicken feathers (45%), and practically did not affect the other studied substrates. The degree of hydrolysis of cat, dog, and pig bristles and children's nails did not exceed 3–6%. Conclusions. Among the investigated keratin-containing substrates, the P. megaterium 035 culture is able to intensively degrade only chicken feathers, which consist mainly of β-keratin.